2023
DOI: 10.3390/fermentation9050422
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Effects of the Cultivation Condition on Different Forms of Peptaibol’s Emericellipsins Production from an Alkaliphilic Fungus, Emericellopsis alkalina

Abstract: Peptaibols (Paib) are a class of biologically active peptides isolated from fungi and molds, which have attracted the attention of medicinal chemists due to their widely ranging pharmacological properties, including their antimicrobial activity. In the present study, we investigated the effects of various pH levels and cultivation conditions on peptaibol complex emericellipsins A-E (EmiA-E), produced by the alkaliphilic fungus Emericellopsis alkalina. Paib production has been studied in flasks and bioreactors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…The strains of fungi were grown on CZA, MYA, and AA. Our prior research demonstrated that an alkaline medium stimulates the synthesis of peptaibols with antimicrobial activity [55][56][57]. The detection of the peptaibol emericellipsin A in the crude extracts from Emericellopsis strains was made by HPLC and MALDI-TOF MS spectra in accordance with previously obtained data [24,58].…”
Section: Antimicrobial Assayssupporting
confidence: 64%
“…The strains of fungi were grown on CZA, MYA, and AA. Our prior research demonstrated that an alkaline medium stimulates the synthesis of peptaibols with antimicrobial activity [55][56][57]. The detection of the peptaibol emericellipsin A in the crude extracts from Emericellopsis strains was made by HPLC and MALDI-TOF MS spectra in accordance with previously obtained data [24,58].…”
Section: Antimicrobial Assayssupporting
confidence: 64%